2011
DOI: 10.1364/ao.50.002283
|View full text |Cite
|
Sign up to set email alerts
|

White-light channeled imaging polarimeter using broadband polarization gratings

Abstract: A white-light snapshot channeled linear imaging (CLI) polarimeter is demonstrated by utilizing polarization gratings (PGs). The CLI polarimeter is capable of measuring the two-dimensional distribution of the linear Stokes polarization parameters by incorporating two identical PGs, in series, along the optical axis. In this configuration, the general optical shearing functionality of a uniaxial crystal-based Savart plate is realized. However, unlike a Savart plate, the diffractive nature of the PGs creates a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(43 citation statements)
references
References 22 publications
0
43
0
Order By: Relevance
“…Note that κα and κβ are constant with wavelength meaning that the carrier frequencies are independent of the illumination's temporal coherence length. This is directly analogous to [8] in that the shear depends linearly on the wavelength. Meanwhile, the complex coefficients A k x; y represent summations of Mueller matrix elements while A a k argA k x; y.…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…Note that κα and κβ are constant with wavelength meaning that the carrier frequencies are independent of the illumination's temporal coherence length. This is directly analogous to [8] in that the shear depends linearly on the wavelength. Meanwhile, the complex coefficients A k x; y represent summations of Mueller matrix elements while A a k argA k x; y.…”
mentioning
confidence: 90%
“…Misregistration is also caused by systematic errors, such as beam-wander from the rotating optical elements. This further increases the complexity in applications where MM imaging polarimetry may be beneficial, especially for in vivo biomedical imaging of scenes with low inherent contrast [6].To eliminate the need for image registration and capture all information in a single measurement (i.e., a snapshot), we propose to combine a technique for channeled Mueller matrix spectropolarimetry [7] with an imaging channeled polarimeter based on polarization gratings (PGs) [8,9]. The layout of the snapshot imaging Mueller matrix polarimeter (SIMMP) is depicted in Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They have concluded that these IR iridescent features have a structural origin at the micrometer level. These authors have performed hyperspectral reflectance polarization imaging [26][27][28] of the Mallard (Anas platyrhynchos) demonstrating that IR iridescence persists in the entire bird [25].…”
Section: Introductionmentioning
confidence: 99%